Dinamika Komunikasi dalam Mewujudkan Kerukunan Hidup antarumat Beragama - Saefullah, Ujang (Jurnal Ilmu Dakwah, 2011)
The dynamic of communication between religion follower ever be fluctuative from time to time, the process sometimes easy going and  at a dead set. If  between follower express attitude with mutually prices , the condition become comfortable, peace and harmonious. Meanwhile, if enmity attitude in front, so the atmosphere become fear, convulsively and disharmony. In stance Sukabumi city, the  dynamics of communication  can bear innovation that add models of communication especially in relation between religion follower context as: interference model of communication, management of religion prominent model, and competition between religion group model.